Pengukuran Efektivitas Kinerja Mesin Rapier 180 Menggunakan Metode Overall Equipment Effectiveness (OEE) - Suci, Dewina Sekar; Rahmawati, Nofa Dwi; Nugrahadi, Bekti (Fakultas Teknik Universitas Tulang Bawang, 2025)
Optimal and maximal production is determined by three factors there is machines, raw material and human. PT AM is a weaving company which use Rapier 180 Loom machines in their process production. In the last five months, historically, the production of the Rapier 180 engine at PT. AM shows a comparison of the quality of grades A was decreased. So, it is necessary to measure the performance of the Rapier machine as an evaluation for the company to determine the next step. The observation method used is the OEE (Overall Equipment Effectiveness) which is a method to evaluate the magnitude of the performance and reliability of a machine. Several data are need for calculation about the Rapier 180 such as target production, actual production, product defects, target run hours, actual run hours, and stop hours. Based on OEE calculations, we find that the Rapier 180 machines in PT AM have a avaibility rate 96%, performance rate 96%, and Quality rate 57% base from that we find OEE of rapier is 52% and based on JIPM (Japan Institute of Plant Maintenance) the performance of the machine is classified as reasonable production but shows that there is still a lot of room for improvement. The factors that cause the OEE value of the Rapier 180 engine to only reach 52% are the lack of maintenance, lack of control and quality checks, and the environment around the machine. Keywords: Effectiveness, OEE, Performance, Production Process, Rapier Machine